A Challenge Beyond Bottom Cells: Top‐Illuminated Flexible Organic Solar Cells with Nanostructured Dielectric/Metal/Polymer (DMP) Films. (2nd June 2015) - Ham, Juyoung; Dong, Wan Jae; Park, Jae Yong; Yoo, Chul Jong; Lee, Illhwan; Lee, Jong‐Lam
<x xml:space="preserve">Abstract</x> Top‐illuminated flexible organic solar cells with a high power conversion efficiency (≈6.75%) are fabricated using a dielectric/metal/polymer (DMP) electrode. Employing a polymer layer (n = 1.49) makes it possible to show the high transmittance, which is insensitive to film thickness, and the excellent haze induced by well‐ordered nanopatterns on the DMP electrode, leading to a 28% of enhancement in efficiency compared to bottom cells.